THE INFLUENCE OF GRANDPARENTING ON COGNITIVE FUNCTION AND THE MEDIATING ROLE OF HEALTH FACTORS. (11th November 2018) - Amano, T; Shen, H; Sun, F
Abstract: Emerging evidence suggests that caring for grandchildren is associated with higher cognitive function of the grandparents. However, age effects on the mechanism behind the association between grandchildren caregiving and cognitive function are still unclear. This study aims to 1) examine to which extent caring for grandchildren is associated with cognitive function in middle-aged and older groups and 2) assess whether such a relationship is mediated by health in each group. Data come from 2010 and 2012 Health and Retirement Study. Including older adults who were 51+ in 2010 and were self-interviewed in both waves, the final sample was composed of 8, 761 middle-aged (51–64) and 8, 571 older (65+) people. Caring for grandchildren was measured as whether the respondent spent 100+ hours taking care of grandchildren during the previous year of the survey. Cognitive function was assessed using Telephone Interview for Cognitive Status. Bivariate analyses revealed that middle-aged caregivers had lower cognitive function and worse health than middle-aged non-caregivers (p<.001); whereas older caregivers had higher cognitive function and better health than older non-caregivers (p<.001). Results of the multiple mediation analysis suggested that the association between caring for grandchildren and cognitive function was mediated by physical health in the older group (p=.039); whereas such a relationship was not found in the middle-aged group (p=.579). Our findings suggest that facilitating grandparenting may be one strategy to prevent cognitive decline in older grandparents but further investigation is urged to unfold the mechanisms of why caregiving is associated with lower cognitive function among middle-aged grandparents.